The long goodbye: the relationship between lleftist parties and the Italian General Confederation of Labour (CGIL) after the end of the Italian Communist Party (PCI) (1992-2017) - Mimmo Carrieri (SER Social)
This article explores the effects of the growth of the “cartel parties” within the Italian system and the new relations between the unions and leftist parties, going beyond the models and experiences of the twentieth century. One of the consequences concerns the stronger interdependence of the parties and the state, and their need for more public resources. Another aspect relates to the relationship of the party with society and other socially representative organisations and stakeholders. In the case of Italy, the Democratic Party, set up in 2007, embodies the weak-minded party version, progressively dismantling the relationship with the trade union movement and, in particular, with the CGIL. The Italian situation confirms that underlying these evolutions there are not only external factors, such as globalisation and changes in the work world, but also internal factors, such as the logic of actions, drawn up and put aggressively into practice by the “cartel parties".